PENGARUH LIFESTYLE TERHADAP KEPUTUSAN PEMBELIAN PRODUK CLOTHING LINE (Survei pada Konsumen Clothing Line Famo di Kota Bandung) - Hilmi, Rafiqi Zul; Hurriyati, Ratih; Lisnawati, Lisnawati (Journal of Business Management Education (JBME), 2018)
Purpose - This study aimed to gain a sense o1qf lifestyle, an overview of purchase decision, and the influence of lifestyle on purchase decision employee performanceDesign / methodology / approach - The method used is an Explanatory Survey with a sample size of 130 respondents. The data analysis technique used is simple linear regression with spss 22.0 for windows programming tool.Findings- Research results show that lifestyle is in the good category, and purchase decision is in the good category. Lifestyle have a positive and significant influence on purchase decision.Originality / value - This study provides a basis for understanding the style of leadership and work motivation that affects employee performance. The difference of this research with previous research is located on the object of research that is CV. Biensi Fesyenindo company and use theory or reference different from previous researcher